Study of Hard Coral Community Structure and Natural Recruitment on Rote Island in the Sawu Sea Marine National Park (TNP) - Idris Idris; Fakhrurrozi; Ofri Johan; Jotham S R Ninef; Edwin Jefri; Mahardika Rizqi Himawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Rote Island and its surroundings are included in the Savu Sea Marine National Park (TNP) area and are administratively included in the Rote Ndao Regency, East Nusa Tenggara (NTT) Province. The waters of the area have high potential for coral reef ecosystem resources and are an important for the marine biota. But when the condition is under pressure due to anthropogenic and natural influences. Therefore it is necessary to carry out routine observations related to the condition of the community structure and its potenstial natural recruitment. Observations were made on 26-28 September 2021 at 12 observation stations. The observation method used was the belt transect method with 3 repetitions (20 m) with an area of 60 m2. Data collection using SCUBA equipment at a depth of 5-7 m on the reef flat. The results of the study found a total of 37 hard coral genera and the highest species richness was in Daiama 2 (30 genera) and the lowest was in Oelua and metina (13 genera). The dominant hard coral genera found were the Porites genera. Furthermore, the potential for natural recruitment of hard coral tillers reaches 21%. The highest potential for natural recovery is at Sotimori 1 (station 3) and the lowest at Boni (station 12). In general, the hard coral community structure at the observation site is in a stable condition with good natural recruitment potential.